O ENSINO DE PROBABILIDADE GEOMÉTRICA: DESAFIOS E POSSIBILIDADES - Ritter, Denise (2017)
Whereas the content of Geometric Probability is usually not worked in math class, this dissertation presents the results of a survey that sought to investigate what are the contributions of teaching Geometric Probability in learning the concept of Probability. The participants of this research were students of the junior year of high school from a school in the municipality of Santa Maria. The activities were organized in a learning unit, structured according to the methodological approach of the Three Pedagogical Moments (TPM) proposed by Delizoicov and Angotti (1990). The resources used in the development of the learning unit were practical experiments, manual and digital games, computational simulation, videos, problem situations and the GeoGebra software. The theory behind this study regarding the development of learning is the Significant Learning. This research is qualitative, with the following tools for its data collection: questionnaires (pre-test and post-test), the records of students and participant observation. The discovery that the students presented difficulties in concepts of areas of geometric shapes in two dimensions was made. Thus, it can be concluded that the activities developed in this research have contributed with the students as to reinforce the concepts of areas of geometric shapes in two dimensions, and also they have helped understand the concepts of probability, promoting meaningful learning of them. It was also noticed that the developed activities stimulated students' autonomy, their creativity and engagement to work in group, a fundamental characteristic to learn to deal with and overcome the challenges that are presented daily.